Needle aspiration in peritonsillar abscess: our experience in Chitwan - Limbu, Tilak Raj; Baral, Sovit Jung; Jha, Amit; Lamichane, Donjon (Journal of Chitwan Medical College, 2020)
Background: Peritonsillar abscess is one of deep neck space having significant morbidity and mortality. The treatment is still controversial regarding best method to perform. The aim of the study was to study the effect of needle aspiration in the treatment of peritonsillar abscess among the patients of Chitwan Medical College. Methods: A retrospective study was designed which included all aged patients and were admitted in tertiary centre for peritonsillar abscess treatment between January 2015 to December 2019. All patient was treated with needle aspiration method under local spray anaesthesia and intravenous antibiotics. Number of aspirations, hospital stay, recurrence and complications were assessed as main outcomes. Descriptive analysis was performed by using SPSS version 16.0. Results: Over 5-year duration, 57 patients were admitted for PTA and included for analysis. About 45(78.9%) of patients were under 40 years. Male dominance of 41(71.6 %) was found. All cases were unilateral and no significant laterality found. All patients had prior medications outside before hospital visit. Length of hospital stay was 3.11+/-.939 days. Single or repeat aspiration of pus showed significant improvement of symptoms. One patient had recurrence and another one case had developed complication. Conclusions: Our study showed needle aspiration is effective modality for peritonsillar abscess treatment due to early clinical improvement, low recurrence and decrease hospital stay.